Effect of Ratio of Purple Sweet Potato with Water and Starter Concentration on Quality of Probiotic Drink from Purple Sweet Potato Juices - Wenni Frisnawati Siregar; Sentosa Ginting; Lasma Nora Lubis (Universitas Sumatera Utara, 2014)
This research was conducted to determine the effect of ratio of purple sweet potato with water and starter concentration on quality of probiotic drink from purple sweet potato juices. This research was performed in May 2013 – July 2013 at the Laboratory of Food Technology, Faculty of Agriculture, University of Sumatera Utara, Medan, using completely randomized design with two factors, i.e. : the ratio of purple sweet potato with water (P) (1 : 1;1 : 2; 1 : 3; 1 :4) and starter concentration (S) (1%, 2%, 3%, 4%). Parameters analyzed were pH , total acid (%),total soluble solid (0brix), total microbial (CFU/g), viscosity (mPa-s), protein content (%), organoleptic values of taste, flavor, and color. The results showed that the effect of ratio of purple sweet potato with water had highly significant effect on pH , total acid (%),total microbial (CFU/g), viscosity (mPa-s), protein content (%), and organoleptic values of color. Starter concentration had highly significant effect onpH , total acid (%), viscosity (mPa-s), protein content (%), organoleptic values of color, flavor, taste and texture. Interactions of the two factors had highly significant effect on moisture content, total acid (%), total soluble solid (obrix), organoleptic values of taste, flavor and color. Ratio of purple sweet potato with water of (1 :2) and starter concentration of (2%) resulted in the best and more acceptable probiotic drink from purple sweet potato juices. Keywords: probiotic drink, Ratio of purple sweet potato with water, starter concentration.